2017
DOI: 10.1177/1748895817728381
|View full text |Cite
|
Sign up to set email alerts
|

Practitioner (mis)understandings of coercive control in England and Wales

Abstract: Coercive control is harmful behaviour recently criminalized in England and Wales. The extent to which the work of practitioners is informed by an understanding of coercive control therefore requires investigation. Using data from two mixed methods multi-site studies, this article suggests that practitioners’ recognition of coercive control does not seem to be universally poor or skilled, but rather depends on the characteristics of the situation itself, the organizational context in which practitioners work an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 36 publications
0
29
0
1
Order By: Relevance
“…Early evaluations of the English legislation point to problems for frontline police officers in 'seeing' coercive control (Wiener 2017), in practitioner understandings of coercive control more generally (Brennan et al 2018;Robinson, Myhill and Wire 2018) and problems associated with providing evidence of this offence (Bishop and Bettinson 2018). However, despite mixed evaluations of its early operation, like offences have continued to emerge in nearby jurisdictions, including the aforementioned Scottish offence and most recently, the introduction of a new offence of coercive control in Ireland, under section 39 of the Domestic Violence Act.…”
Section: A Specific Offence Of Coercive Controlmentioning
confidence: 99%
“…Early evaluations of the English legislation point to problems for frontline police officers in 'seeing' coercive control (Wiener 2017), in practitioner understandings of coercive control more generally (Brennan et al 2018;Robinson, Myhill and Wire 2018) and problems associated with providing evidence of this offence (Bishop and Bettinson 2018). However, despite mixed evaluations of its early operation, like offences have continued to emerge in nearby jurisdictions, including the aforementioned Scottish offence and most recently, the introduction of a new offence of coercive control in Ireland, under section 39 of the Domestic Violence Act.…”
Section: A Specific Offence Of Coercive Controlmentioning
confidence: 99%
“…In the United States, judges are required to take into consideration allegations of DV when making child custody decisions (American Bar Association, ); however, in policy, the focus is still on discrete acts of physical violence without attention to the context in which the violence occurs. In contrast, coercive control has been an explicit part of the U.K. government's definition of DV since 2013, and in 2015, the United Kingdom began legislating coercive control within an intimate or family relationship as a criminal offense in Section 76 of their Serious Crime Act (Robinson, Myhill, & Wire, ). It is important to note, however, that legislation does not guarantee proper practical application.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note, however, that legislation does not guarantee proper practical application. Robinson et al (), for example, found that English and Welsh police officers were often unaware of what coercive control entails, how they should identify it, and the potentially negative implications for misunderstanding the construct.…”
Section: Discussionmentioning
confidence: 99%
“…For example, including risk items such as 'strangulation' and 'controlling behaviour' may encourage police officers to investigate for these factors. With regards controlling and coercive behaviour, this might be critical because it can have a profound impact on the victim but may not be immediately apparent to police officers without probing questions (Myhill & Hohl, 2016: Robinson, Pinchevsky, & Guthrie, 2016bRobinson, Myhill, & Wire, 2017). Requiring officers to rate this factor may encourage a greater depth of investigation than would otherwise occur.…”
Section: Practical Aspects Of Applying Intimate Partner Violence Riskmentioning
confidence: 99%